Yeast tolerance to the ionic liquid 1-ethyl-3-methylimidazolium acetate. Issue 8 (1st December 2014) - Sitepu, Irnayuli R.; Shi, Shuang; Simmons, Blake A.; Singer, Steven W.; Boundy-Mills, Kyria; Simmons, Christopher W.
Abstract: Lignocellulosic plant biomass is the target feedstock for production of second-generation biofuels. Ionic liquid (IL) pretreatment can enhance deconstruction of lignocellulosic biomass into sugars that can be fermented to ethanol. Although biomass is typically washed following IL pretreatment, small quantities of residual IL can inhibit fermentative microorganisms downstream, such as the widely used ethanologenic yeast, Saccharomyces cerevisiae . The aim of this study was to identify yeasts tolerant to the IL 1-ethyl-3-methylimidazolium acetate, one of the top performing ILs known for biomass pretreatment. One hundred and sixty eight strains spanning the Ascomycota and Basidiomycota phyla were selected for screening, with emphasis on yeasts within or closely related to the Saccharomyces genus and those tolerant to saline environments. Based on growth in media containing 1-ethyl-3-methylimidazolium acetate, tolerance to IL levels ranging 1–5% was observed for 80 strains. The effect of 1-ethyl-3-methylimidazolium acetate concentration on maximum cell density and growth rate was quantified to rank tolerance. The most tolerant yeasts included strains from the genera Clavispora, Debaryomyces, Galactomyces, Hyphopichia, Kazachstania, Meyerozyma, Naumovozyma, Wickerhamomyces, Yarrowia, and Zygoascus . These yeasts included species known to degrade plant cell wall polysaccharides and those capable of ethanol fermentation. These yeasts warrant further investigation for use in saccharification and fermentation of IL-pretreated lignocellulosic biomass to ethanol or other products. Tolerance to an ionic liquid relevant to biomass pretreatment for biofuel production is discovered in several yeast species, raising potential for yeast fermentation of pretreated biomass containing residual IL. Tolerance to an ionic liquid relevant to biomass pretreatment for biofuel production is discovered in several yeast species, raising potential for yeast fermentation of pretreated biomass containing residual IL.